Analisis Pengaruh Jarak Excavator terhadap Stabilitas Dinding Penahan Tanah Menggunakan Pendekatan Beban Garis (Studi Kasus: Konstruksi Kanal di Batam) - Ryan Maulana; Junaidi Junaidi (Universitas Batanghari Jambi, 2026)
The operation of heavy equipment during construction activities generates additional loads that may affect the stability of retaining walls, particularly when the equipment operates close to the structure. In the construction project of a luxury accommodation complex in Batam City, the canal structure at STA 0+220–0+230 experienced an overturning failure, which was presumed to be influenced by the operational load of a Hyundai R140LC-9S excavator. This study aims to analyze the effect of excavator operating distance on retaining wall stability using a line load approach. The research employed an analytical method through manual calculations of lateral earth pressure, overturning stability, sliding stability, and bearing capacity under the existing condition, followed by manual line load calculations obtained by simplifying the excavator load and evaluating the effect of different excavator operating distances on the safety factors. The results indicate that the safety factors for overturning, sliding, and bearing capacity under the existing condition were 2.337, 1.676, and 4.245, respectively. When the excavator operated at a distance of 2 m, the safety factors decreased to 1.831, 1.306, and 1.907, respectively. At an operating distance of 4 m, the safety factors increased to 2.128, 1.514, and 3.021, respectively, satisfying the minimum requirements specified in SNI 8460:2017. Therefore, the closer the excavator operates to the retaining wall, the greater the reduction in stability. Among the operating distances evaluated in this study, 4 m was the shortest distance that satisfied all safety-factor requirements specified in SNI 8460:2017.